Economic theories of the entrepreneur: A systematic review of the literature - Brown, Christopher Russell (Cranfield University, 2007)
Economic theories of the entrepreneur have received more attention recently in the entrepreneurship literature. Different concepts and ideas are typically borrowed from various economists to create new, or expand upon existing, theories. This has created a somewhat fragmented literature, and I found no evidence of a previous systematic (or comprehensive literature) review of any economic theories of the entrepreneur. The many different economic theories of the entrepreneur over time and a renewed interest in researching entrepreneurship within an economics framework led to my research questions: What are the different economic theories of the entrepreneur? What are the main themes and sub themes of these economic theories? The aims of my systematic review were: (1) to provide a literature scoping section that gives an overview of the economics and entrepreneurship fields which lead to my research question; (2) to develop a systematic review protocol which outlines the various stages of the review process which will answer the review question; and (3) to carry out the review by locating and synthesizing the relevant literature. The process proved beneficial as evidenced by the comprehensiveness of the findings. The most influential school of economics on the field of entrepreneurship is arguably the Austrian school, with Israel Kirzner as the main developer of an economic theory of the entrepreneur. Most of the current themes in the entrepreneurship literature come from his theory and future research in entrepreneurship appears to be moving forward with ideas from the Austrian school. I have synthesized the results from the systematic search and identified 7 major recurring themes in the literature: entrepreneurial opportunity identification and exploitation; discovery; knowledge; uncertainty and risk; the market as a process; disequilibrium; and alertness. Taken together, these themes provide a clearer picture of the economic function of the entrepreneur.